Budaya Organisasi Dan Gaya Kepemimpinan - Prawoto, Budi (Fakultas Ekonomi Universitas Wisnuwardhana, 2014)
In giving an optimum service to the people of BirocrateGovernmental, it needs much of humman source who are skillfulland professional in implementing its task. Human source is anasset which is essential in an orgnization, thus it needs apreception,perception , that becomes the system of value and itneeds a consistency of leadership. So that the level of workingsatisfactory could be established and affect in such the occurenceof purpose of the organization.Keyword: culture of organization, leadership style, workingsatisfactory